Study of the Na Storage Mechanism in Silicon Oxycarbide—Evidence for Reversible Silicon Redox Activity. Issue 4 (6th August 2018) - Dou, Xinwei; Buchholz, Daniel; Weinberger, Manuel; Diemant, Thomas; Kaus, Maximilian; Indris, Sylvio; Behm, Rolf J.; Wohlfahrt‐Mehrens, Margret; Passerini, Stefano
Abstract: Silicon‐based compounds are interesting candidate anode materials but show only relatively low electrochemical performances with sodium. Controversial reports are available about the electrochemical interaction between Na and silicon, which encourage to investigate the mechanism in a silicon‐based material in detail. This study reports the results of a systematic investigation of the electrochemical sodium ion storage in silicon oxycarbide (SiCO) using ex situ X‐ray photoelectron spectroscopy and magic‐angle spinning nuclear magnetic resonance spectroscopy. Comparison of pristine and hydrofluoric acid‐etched silicon oxycarbide shows that the silicon oxycarbide is active itself, but not by an alloying process. Instead, results reveal an irreversible structural change and amorphization of SiCO upon the initial sodium uptake and support the existence of reversible insertion‐based reactions in the subsequent cycles. Abstract : A systematic investigation of the electrochemical sodium ion storage in silicon oxycarbide (SiCO) is reported. In this mechanistic study, reversible redox activity of Si during an insertion process is proved; furthermore, the existence of an alloying reaction between sodium and silicon or a reversible conversion reaction to form silicon carbide (SiC) is excluded.